2021
DOI: 10.31234/osf.io/nyd8a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Big Five traits as Predictors of Perceived Stressfulness of the COVID-19 Pandemic

Abstract: This study examined the Big Five personality traits as predictors of individual differences and changes in the perceived stressfulness of the COVID-19 pandemic in Germany between early April 2020 and early September 2020. This timeframe includes the first national “lockdown,” the period of “easing” of restrictions, and the summer vacation period. Data were collected from n = 588 full-time employees, who provided baseline data on their personality traits in early December 2019, and then later provided data on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 27 publications
1
22
0
2
Order By: Relevance
“…Moreover, event system theory (Morgeson et al, 2015) and transition-adaptation theories (Bliese et al, 2017) can be fruitfully integrated to explain how employees initially react to and, over time, recover from crisis events (e.g. lockdowns), for instance in terms of perceived stressfulness (Zacher and Rudolph, 2021a) or self-rated work performance (Zacher et al, 2021).…”
Section: Theory Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, event system theory (Morgeson et al, 2015) and transition-adaptation theories (Bliese et al, 2017) can be fruitfully integrated to explain how employees initially react to and, over time, recover from crisis events (e.g. lockdowns), for instance in terms of perceived stressfulness (Zacher and Rudolph, 2021a) or self-rated work performance (Zacher et al, 2021).…”
Section: Theory Developmentmentioning
confidence: 99%
“…In the current paper, we take a step back and reflect on what we have learned about researching employee experiences and behavior in times of crisis in the years 2020 and 2021, based on our own conceptual and empirical work on the COVID-19 pandemic and employee experiences and behavior (Rudolph and Zacher, 2021b;Zacher et al, 2021;Zacher and Rudolph, 2021a;Zacher and Rudolph, 2021b), as well as the work of our colleagues. We first review theoretical approaches that (could) have been applied to understand changes in employee experiences and behavior during the COVID-19 pandemic, as well as theoretical approaches that could be applied to examine these phenomena during future crises.…”
Section: Introductionmentioning
confidence: 99%
“…All these drastic workplace changes increased emotional stress and concerns for the health and safety of loved ones as well as oneself (Kocjan, Kavčič, & Avsec, 2021; Xiong et al, 2020). Previous research has suggested stressors such as these are likely to lower employee well-being (Mojtahedi et al, 2021; Zacher & Rudolph, 2021), and in turn decrease job productivity (Toscano & Zappalà, 2020) and strain workplace relationships (Kaushik & Guleria, 2020). Against this backdrop, this study focuses on three outcome variables pertinent to workers worldwide during the early days of the COVID-19 pandemic: psychological well-being, productivity, and relational satisfaction at work (Galanti, Guidetti, Mazzei, Zappalà, & Toscano, 2021; Kaushik & Guleria, 2020; Kniffin et al, 2021).…”
Section: Well-being Productivity and Relational Satisfaction During Covid-19mentioning
confidence: 99%
“…In this study, psychological well-being is defined as one's levels of positive affective states, functioning, and quality of life (Topp, Østergaard, Søndergaard, & Bech, 2015; Winefield, Gill, Taylor, & Pilkington, 2012). The impact of COVID-19 on employee well-being has been well-documented with multiple studies reporting an increase in employees' anxiety, depression, and stress compared to the pre-pandemic era (Labrague & De los Santos, 2020; Mojtahedi et al, 2021; Zacher & Rudolph, 2021).…”
Section: Well-being Productivity and Relational Satisfaction During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation